Neumann's Tumor - A Rare Neonatal Tumor - Ceyhan Sahin; Zeliha Akış yıldız; Aytekin Kaymakcı; Ozgül Gergin tinay (EL-Med-Pub, 2018)
Neumann's tumor, also known as congenital granular cell tumor, congenital myoblastoma, congenital epulis, was first described by Neumann in 1871. It's a rare cause of newborn's intraoral masses. they are usually on the maxilla and soliter , they can rarely  be seen on the mandibula and multiple. Even if it is not clinically symptomatic, surgical resection is performed because of its cosmetic appearance, negative psychological effect on the family , differential diagnosis and treatment. Neumann's tumor is fully cured by surgical resection because it does not show recurrence or metastasis after excision.